Clinical and immunological biomarkers in hypereosinophilic syndrome: the second step after diagnostic algorithms - Longhino, David; Baglivo, Ilaria; Zavarella, Maria Antonietta; Colantuono, Stefania; Laface, Chiara; Lucca, Gabriele; Bruno, Laura; Selvi, Fabio Romano; Patella, Vincenzo; Detoraki, Aikaterini; Buonagura, Rosa; Tatarelli, Caterina; et al. (Frontiers in Medicine, 2025)
BackgroundIdiopathic hypereosinophilic syndrome currently represents a major unmet need for all medical specialties dealing with this disease. Markers capable of characterising the wide variability of its clinical presentation are currently lacking.ObjectiveThis study aims to evaluate a panel of possible markers in idiopathic hypereosinophilic syndrome.MethodsIn this pilot prospective single-centre cohort study, we analysed clinical (age, years of disease, steroid therapy) and laboratory (absolute eosinophil count, total IgE antibodies, IgE antibodies against Staphylococcus aureus enterotoxins, serum eosinophil cationic protein, serum immunoglobulin free light chains k and λ and their ratio) data obtained from 21 patients suffering from idiopathic hypereosinophilic syndrome from June 2023 to December 2024.ResultsMean absolute eosinophilic count was 3758.57 cells/μL. 17 patients were receiving treatment with > 7.5 mg of prednisone or equivalent at the time of the diagnosis. 13 patients had positive Staphylococcus aureus enterotoxins IgE, while the mean total serum IgE was 241.64 kU/L. We observed a high serum eosinophil cationic protein value as well as a high serum κ free light chain, while serum λ and κ/λ were normal. Patients with higher absolute eosinophilic count had higher eosinophil cationic protein levels (p < 0.05), such as higher steroid consumption (p < 0.05). In addition, we found a strong association between high κ free light chain levels and high previous steroid use and with Staphylococcus aureus enterotoxins IgE positivity.ConclusionOur results could increase the number of possible biomarkers for risk stratification in idiopathic hypereosinophilic syndrome.